2020
DOI: 10.2174/1381612825666191212105145
|View full text |Cite
|
Sign up to set email alerts
|

The Prevention and Inhibition Effect of Anthocyanins on Colorectal Cancer

Abstract: Background: Anthocyanins are a type of flavonoids that are natural water soluble glycosidic pigments with efficacious anti-cancer effects, which have good biological activity against many cancers including colorectal cancer (CRC). However, the exact molecular mechanism used by anthocyanins against cancer is unclear; it is also unclear what a reasonable dosage might be for their use against colorectal cancer. Methods: Western blotting, immunohistochemistry, MTT assay, xenograft model, and hematoxylin-eosin (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…Previous studies have demonstrated that the PI3K/AKT pathway played a key role in modulating cell proliferation and apoptosis [14,15]. In glioma studies, multiple evidences revealed that the activation of PI3K/AKT pathway could enhance cell proliferation in a mTOR dependent or independent way [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the PI3K/AKT pathway played a key role in modulating cell proliferation and apoptosis [14,15]. In glioma studies, multiple evidences revealed that the activation of PI3K/AKT pathway could enhance cell proliferation in a mTOR dependent or independent way [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…All the cell lines responded in a similar manner, in which there was an increased inhibition of cell growth as the concentration of berry extract increased [9]. Anthocyanins may be particularly effective against colorectal cancer [9,[71][72][73][74][75], with evidence from a meta-analysis by Wang et al suggesting a significant inverse relationship between total anthocyanin consumption and risk of colorectal cancer development [74]. Anthocyanins derived from the six berry species mentioned prior and the grumixama fruit may be particularly effective against breast cancer [9,76].…”
Section: Cancermentioning
confidence: 92%
“…Increased cell proliferation and decreased apoptosis are factors that lead to the development and progression of cancer [68]; anthocyanins may have an effect on these processes [9,13,16,[69][70][71][72][73][74][75]. The mechanism of action is unconfirmed, with multiple mechanisms likely working in tandem [71].…”
Section: Cancermentioning
confidence: 99%
“…Ali et al demonstrated that anthocyanins can regulate PI3K Akt signaling pathway in AD mice [93]. Zhao et al found that anthocyanins could down regulate the expression of PI3K protein and inhibit the expression and phosphorylation of Akt [94]. In conclusion, a number of studies have shown that anthocyanins inhibit COX activity, reduce PGE2 production, and reduce inflammation by inhibiting NF-κB and PI3K Akt signaling pathways.…”
Section: Prostaglandin E2 (Pge2)mentioning
confidence: 98%